Case report: Multicomponent intervention for severe food selectivity in autism spectrum disorder: a single case study - Maggio, Roberta; Turriziani, Laura; Suraniti, Silvana; Graziano, Maria; Patanè, Santina; Randazzo, Anna Maria; Passantino, Claudio; Di Cara, Marcella; Quartarone, Angelo; Cucinotta, Francesca (Frontiers in Psychiatry, 2024)
Food selectivity is common in children with Autism Spectrum Disorder (ASD). The treatment used can be invasive and difficult to implement, necessitating the exploration of a multicomponent approaches. This study presents the case of a 9-year-old autistic girl with severe food selectivity, who ate exclusively liquid and semi-solid foods. A multicomponent intervention protocol was developed, including stimulus fading and positive reinforcement techniques, to increase acceptance of new textures and foods. Treatment sessions showed significant improvement in acceptance of semi-solid and novel foods, with a reduction in problem behaviors associated with mealtime. This study suggests that a multicomponent intervention can significantly improve food acceptance and reduce mealtime distress, proving to be a practical and effective treatment strategy in an autistic child. The case demonstrates the effectiveness of an integrated, individualized approach to treating food selectivity in children with ASD. The intervention led to an increase in food acceptance and a reduction in mealtimerelated distress, potentially improving the child and family's quality of life.